Teacher’s perspective on inclusive education during remote teaching of primary school students with individual educational needs - Iwona Chrzanowska (Studia z Teorii Wychowania)
Remote education during the COVID-19 pandemic has become a challenge for educational practice worldwide. Students with individual educational needs found themselves in an unusual situation. The article presents the results of qualitative research conducted on a group of 34 teachers of older primary classes (IV-VIII) who, during the pandemic, had among the children they were teaching students with individual educational needs. The research aimed to identify how the experiences of remote education of students with individual educational needs translate into the perception of the challenges facing inclusive education. As a result of the research, relevant problem categories were recognized. Two of them: the activity of students with individual educational needs in online lessons (1) and parental support (2), are discussed in the text of the article